The determinants of household debt in Malaysia / Muhammad Najmi Abu Bakar - Abu Bakar, Muhammad Najmi (2016)
The objective of this study to study about “The Determinants of the Household debt in Malaysia”. The variables that were chosen in this study were household debt to GDP ratio as the indicator for the household debt that has been rise in the recent years caused by variables such as Gross Domestic Product (GDP), Interest Rate, and House Price Index (HPI). Several tests are used to earn the result of this study such as T-statistic test, test of overall significant (F-test multicollinearity test and autocorrelation test. The annual data was collected year 1986 until 2014 and the data have been run using Eviews 8. The result shows there have significant between household debt and gross domestic product and house price index. Meanwhile, interest rate was not significant with the household debt